Eine Gruppe Nudisten auf dem Gelände Thielle am Neuenburgersee, um 1982
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Friedensbewegung politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Jugendbewegung